The global financial crisis and the evolution of markets, institutions and regulation - Moshirian, Fariborz (Journal of Banking & Finance, 2011)
This paper analyses the recent global financial crisis in the context of the dual processes of market development and regulation. It discusses how, in the absence of a globally integrated financial framework, past and present regulations and interventions in reaction to national and global financial crises did not resolve the cross border regulatory arbitrage. The paper discusses how crises often lead to the emergence of new national and international institutions. It also analyses the proposed “new global framework” that needs to be in place if the policy recommendations contained in the G20 communiqué are going to be effectively implemented. The paper argues that unless international agreements are ratified by all nations and become part of national rules and laws, the presence of regulatory arbitrage and the lack of adequate cross border information and data may prevent the global economy from addressing the underlying causes of the recent global financial crisis. The paper also discusses the evolution of central banks and their new role in contributing to global financial stability. The paper argues that the recent global financial crisis has provided a unique opportunity to go beyond economic data and attempt to capture cross border financial data and other information that could assist international and national institutions to measure and manage financial risk more effectively. Finally, the paper discusses “too big to fail” and argues that only an internationally integrated financial system will make large banks global, both when operational and in the event of insolvency.